Deciphering the impact and mechanism of Trikatu, a spices-based formulation on alcoholic liver disease employing network pharmacology analysis and in vivo validation - Sharma, Ruchi; Jadhav, Mangala; Choudhary, Neha; Kumar, Arun; Rauf, Abdur; Gundamaraju, Rohit; AlAsmari, Abdullah F.; Ali, Nemat; Singla, Rajeev K.; Sharma, Rohit; Shen, Bairong (Frontiers in Nutrition, 2022)
Trikatu Churna (TC) comprising Zingiber officinale rhizome, Piper longum, and Piper nigrum fruit, is effective in treating liver diseases and has high nutraceutical values. However, the efficacy of TC in treating alcoholic liver disease (ALD) and its mechanism remain largely unknown. This study evaluated the hepatoprotective effects of different doses of TC as well as to identify the bioactive components and determine their mechanism of action against ethanol-induced ALD. A compound-target network analysis model of TC was established to identify its potential bioactive compounds and pathways that might regulate its hepatoprotective effects. Further, in-vivo studies were performed to validate the potential of TC (200mg/kg and 400mg/kg b.w.) in the treatment and management of ALD. The study revealed that both the dosages of TC demonstrate significant(p>0.0001) hepatoprotective effects by improving body weight, total bilirubin, serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT), serum alkaline phosphate (ALP),SGOT, SGPT, ALP, total cholesterol, total protein, globulin, albumin, and liver morphology. The High-performance thin-layer chromatography (HPTLC) fingerprinting of TC showed the presence of piperine. Network pharmacology identifies the role of TC in regulating various signaling processes including Advanced glycation end products- receptor for advanced glycation end products (AGE-RAGE), Hypoxia-inducible factors (HIF-1), Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-Kappa B), and Phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) signaling to exert its anti-inflammatory, antioxidant and anti-apoptotic role in managing ALD. Based on the bioinformatics analysis, some of the key targets of TC were found to be Prostaglandin-Endoperoxide Synthase 2 (PTGS2) or Cyclooxygenase-2 (COX-2), Sirtuin 1 (SRT1), and caspase-3. These effects may serve as a novel therapeutic option for the treatment of ALD. These preclinical validation studies for the ethnopharmacological potential of TC in ALD treatment further paved the way for researchers to perform next-level translational and clinical studies. Further, in-depth experimental studies for the validation of these bioinformatics-based results will give a clearer picture of mechanisms.